Comparison of phenolic content and antioxidant activity of fresh and fried local fruits - Ahmad Jelani, Nur Arina; Azlan, Azrina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Fried fruits are popularly consumed by many people over the world. Some of the famous local fried fruits are fried cempedak, jackfruit and breadfruit. These fruits are rich in antioxidant, but the antioxidant content after frying is unknown as frying may alter the antioxidant content. This study aimed to compare total phenolic content and antioxidant activity of fresh and fried local fruits. Freeze-dried samples were extracted using 80% methanol and Folin-Ciocalteu assay was used to determine the total phenolic content (TPC) of the samples while FRAP and Beta-carotene assays were used to evaluate their antioxidant activity. Fried jackfruit (76.836 + 0.619 mg GAE/100g) had the highest TPC, followed by fresh jackfruit, fried cempedak, fresh cempedak, fried breadfruit and the lowest TPC was in fresh breadfruit (54.042 + 0.596 mg GAE/100g). Sample with the highest antioxidant activity as measured by FRAP assay was fresh cempedak (3.881 + 0.301 mM Fe2+/g), followed by fresh breadfruit, fresh jackfruit, fried jackfruit, fried breadfruit and the least antioxidant activity was in fried cempedak (0.794 + 0.106 mM Fe2+/g). Using Beta-carotene assay, fried cempedak had the highest percentage of antioxidant activity (98.936 + 0.182) followed by fresh jackfruit, fresh cempedak, fried jackfruit, fresh breadfruit and the lowest was observed in fried breadfruit (-76.449 + 8.139). There was no correlation found between TPC and antioxidant activity as measured using both FRAP and beta-carotene assays. In conclusion, frying of fruits resulted in increment of TPC but mixed changes in antioxidant activity of the final product thus suggesting the importance of controlling the frying process in getting the benefits of fruit antioxidants.